Enzymatic delignification of sugar cane bagasse and rice husks and its effect in saccharification. (September 2020) - Matei, Jéssica C.; Soares, Marlene; Bonato, Aline Cristine H.; de Freitas, Maria Paula A.; Helm, Cristiane V.; Maroldi, Wédisley V.; Magalhães, Washington L.E.; Haminiuk, Charles W.I.; Maciel, Giselle M.
Abstract: Sugarcane bagasse (SB) and rice husks (RH) are agroindustrial byproducts which can be hydrolyzed to release sugars for the production of valuable bioproducts. However, the exposure of their carbohydrates to the action of hydrolytic enzymes depends on the removal/modification of lignin by a pretreatment. Here we report a biological strategy for pretreatment of SB and RH using a crude enzyme extract rich in laccases to delignification and improvement of reducing sugars yield after saccharification. Enzyme extracts were produced by different species of fungi cultured in a medium with agroindustrial byproducts and other components in static semi-solid condition. The highest yields of laccase production were obtained by Trametes villosa (9467.8 U/L). SB and RH were pretreated with this crude enzyme extract in various conditions and the process optimization resulted in the choice of proper mediators for laccases oxidative action and an increase of more than 10-fold in reducing sugars concentration in the saccharified samples (291 mg/g of sugars were obtained from SB and 193 mg/g from RH) when compared to the control (non pre-treated). Results of MIR-ATR suggested that RH were less susceptible to enzymatic pretreatment than SB and partial removal/modification of lignin was sufficient to improve saccharification. Highlights: Sugarcane bagasse induced the production of laccase by Trametes villosa . Enzyme extract rich in laccases was effective in modifying the lignocellulosic matrix. Tween 80 and 4-hydroxybenzoic acid significantly improved enzymatic pretreament Reducing sugars yield increased more than 10-fold after pretreatment and hydrolysis. Glucose was the main sugar present in SB and RH hydrolysates.